Walrasian Tâtonnement Auctions on the Tokyo Grain Exchange - Eaves, James; Williams, Jeffrey (Review of Financial Studies, 2007)
The Tokyo Grain Exchange (TGE)’s itayose mechanism provides the opportunity to analyze functioning Walrasian tâtonnement auctions (WTA). In 15,677 auctions conducted over 1997–1998 for corn and redbean futures contracts, price formation is unexpectedly similar to that observed in continuous double auctions. Provisional prices and pledges are informative. In contrast to behavior observed in experiments, few pledges are deceptive, because the traders participate repeatedly and because the auctioneer has flexibility when changing the provisional price and ending the auction. Both the risk of the auction ending and the more equitable dispersion of information increase depth and the speed at which information is embodied in price.